Biology of mitral valve prolapse: from general mechanisms to advanced molecular patterns—a narrative review - Ronco, Daniele; Buttiglione, Gianpiero; Garatti, Andrea; Parolari, Alessandro (Frontiers in Cardiovascular Medicine, 2023)
Mitral valve prolapse (MVP) represents the most frequent cause of primary mitral regurgitation. For several years, biological mechanisms underlying this condition attracted the attention of investigators, trying to identify the pathways responsible for such a peculiar condition. In the last ten years, cardiovascular research has moved from general biological mechanisms to altered molecular pathways activation. Overexpression of TGF-β signaling, for instance, was shown to play a key role in MVP, while angiotensin-II receptor blockade was found to limit MVP progression by acting on the same signaling pathway. Concerning extracellular matrix organization, the increased valvular interstitial cells density and dysregulated production of catalytic enzymes (matrix metalloproteinases above all) altering the homeostasis between collagen, elastin and proteoglycan components, have been shown to possibly provide a mechanistic basis contributing to the myxomatous MVP phenotype. Moreover, it has been observed that high levels of osteoprotegerin may contribute to the pathogenesis of MVP by increasing collagen deposition in degenerated mitral leaflets. Although MVP is believed to represent the result of multiple genetic pathways alterations, it is important to distinguish between syndromic and non-syndromic conditions. In the first case, such as in Marfan syndrome, the role of specific genes has been clearly identified, while in the latter a progressively increasing number of genetic loci have been thoroughly investigated. Moreover, genomics is gaining more interest as potential disease-causing genes and loci possibly associated with MVP progression and severity have been identified. Animal models could be of help in better understanding the molecular basis of MVP, possibly providing sufficient information to tackle specific mechanisms aimed at slowing down MVP progression, therefore developing non-surgical therapies impacting on the natural history of this condition. Although continuous progress has been made in this field, further translational studies are advocated to improve our knowledge of biological mechanisms underlying MVP development and progression.